Efektifitas Penggunaan Media Massage Gun Terhadap RPE Atlet Sepakbola - Putra Wardana, Adsya Agnia; Kardjono, Kardjono; Mustaqim, Ridha (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
This study aims to determine the effect of massage gun media on RPE (Rated Percived of Exertion) in soccer athletes. This research uses experimental method with one-group pretest posttest design model. The population of this study were Persib Academy athletes, totaling 30 athletes, ranging the age of 16 years. This population was chosen because training was carried out intensively and training was carried out regularly for 4 times/week. 18 athletes of Persib Bandung Academy made the research subject with purposive sampling technique. The procedure of this study is to provide high-intensity training activities using the Yo-Yo Intermittent test. Recovery Test to determine the RPE scale when after the exercise is finished then give some treatment using Massage Gun with a duration of 15 minutes then re-tested RPE. The research instrument used is RPE or Rated Percived Exertion, RPE is a subjective scale used to measure the level of fatigue or perceived effort on an individual's perception of the intensity of work performed, based on the results of data processing, it was found that the massage method using massage guns had an effect on RPE (Rated Percived of Exertion) significantly. Based on the results of the data processing of hypothesis testing that has been done, it can be concluded that there is a significant effect of the use of Massage Gun significantly affects the decrease in fatigue symbolized by RPE (Rating of Perceived Exertion).